The influence of vibration on muscle activation and rate of force development during maximal isometric contractions - Humphries, B.; Warman, G.; Purton, J.; Doyle, T. L. A.; Dugan, E. (Journal of Sports Science & Medicine, 2004)
At present there appears to be a need for research conducted on the effects of vibration on the contractile ability of skeletal muscle tissue. The aim of this study was to address this issue by examining the effects of a superimposed muscle/tendon vibration at 50.42±1.16 Hz (acceleration 13.24 ± 0.18ms-2: displacement 5mm) on muscular activation and maximal isometric contraction. Sixteen participants with a mean age, body mass, and height of 22 ± 4.4 years, 73.2 ± 11.7 kg and 173.1 ± 9.7 cms, respectively, were recruited for this study. Electromyography and accelerometry from the rectus femoris, and maximal isometric force data characteristics were collected from the dominant limb under conditions of vibration, and no-vibration. A superimposed 50 Hz vibration was used during the contraction phase for the maximal isometric leg extension for the condition of vibration. A one-way ANOVA revealed no significant (p > 0.05) differences between the vibration and no-vibration conditions for peak normalized EMGRMS (84.74% Vs 88.1%) values. An ANOVA revealed significant (p > 0.05) differences between the peak fundamental frequencies of the FFT between the conditions vibration (27.1 ± 12.2 Hz) and no-vibration (9.8 ± 3.5 Hz). Peak isometric force, peak rate of force development, rate of force development at times 0.05, 0.01, 0.1, 0.5 seconds, and rate of force development at 50, 75, and 90% of peak force were not significantly different. The results of this study suggest that the application of vibration stimulation at 50 Hz during the contraction does not contribute to muscle activation, or enhance force production for maximal isometric contractions.